Insight into infectious hematopoietic necrosis virus (IHNV) in Chinese rainbow trout aquaculture from virus isolated from 7 provinces in 2010–2014 - Jia, Peng; Breyta, Rachel B.; Li, Qing; Qian, Xu; Wu, Bing; Zheng, Wei; Wen, Zhiqing; Liu, Ying; Kurath, Gael; Hua, Qunyi; Jin, Ningyi; Liu, Hong (Aquaculture, 2018)
The aquatic rhabdovirus infectious hematopoietic necrosis virus (IHNV) currently causes substantial fish losses in Chinese coldwater aquaculture. While IHNV was first reported in China in 1985 and has since undergone considerable spread, little is known about the underlying epidemiological patterns like introduction sources and transmission routes. In this study, we examined epidemiological and phylogenetic data for 50 IHNV isolates from 7 provinces in China detected in 2010–2014 (Liaoning, n = 33; Jilin, n = 3; Heilongjiang, n = 1; Yunnan, n = 2; Sichuan, n = 1; Hebei, n = 5; Gansu, n = 5). Features of case details include highest mortality associated with water temperatures of 8–10 °C and symptomatic disease observed in adult rainbow trout. Sequence comparisons of the midG sequences of 50 strains revealed 11 different sequence types. One sequence type, mG801J, was predominantly detected, being found in 38 of 50 isolates. Phylogenetic analyses of the new midG sequence types showed that 49 of 50 IHNV isolates are closely related to one another and all descend from the previously described J Nagano subgroup, forming the monophyletic group J Nagano-China clade. This indicates that the majority of IHNV circulating within China is descended from a single importation event from elsewhere in Asia. The one observed exception was the detection of a novel genotype belonging to the previously described MN subgroup. This genotype was identified in Liaoning province, and indicates a second introduction event, one that does not appear to have resulted in diversification and spread. These results indicate that continued surveillance of IHNV in China is necessary to understand and manage viral transmission dynamics within China over time. •A total of 50 positive IHNV isolates were identified from 7 provinces in China in 2010–2014. The 50 strains revealed 11 different sequence types, one sequence type, mG801J, was predominantly detected, being found in 38 of 50 isolates.•The 49 of 50 IHNV isolates are closely related to one another and belong to J Nagano subgroup, J Nagano-Ch clade. The majority of IHNV circulating within China is descended from a single importation event from elsewhere in Asia.•We report firstly a novel genotype belonging to the MN subgroup IHNV in China.•Our results, together with ongoing viral epidemiological surveillance, will provide concrete evidence for the design of management strategies in China.